Wyrażenia emotywne i wzbudzające afekty w zbiorze nowel „Insurgenci. Opowiadania o powstaniach śląskich” (PDF 449 KB) (Książnica Śląska, 2025)
The article is devoted to an analysis of stylistic means in assorted stories from a collection titled Insurgenci. Opowiadania o powstaniachśląskich (Insurgents. The stories about The Silesian Uprisings). Amongthe texts, collected and published by Bolesław Lubosz, a story by PolaGojawiczyńska, titled Górnoślązaczka [The Upper Silesian woman], isparticularly interesting. However, the rest of stories follows the trendof PRL political propaganda and, according to the author, is not attractive for a contemporary reader.